2022
DOI: 10.1002/edn3.315
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lake sedimentary ancient DNA metabarcoding to assess fungal biodiversity in Arctic paleoecosystems

Abstract: Fungi are crucial organisms in most ecosystems as they exert ecological key functions and are closely associated with land plants. Fungal community changes may, therefore, help reveal biodiversity changes in past ecosystems. Lake sediments contain the DNA of organisms in the catchment area, which allows reconstructing past biodiversity by using metabarcoding of ancient sedimentary DNA. We re-evaluated various commonly used metabarcoding primers, and we developed a novel PCR primer combination for fungal metaba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Long‐term changes in fungal communities using the sed DNA approach have been recently used to track catchment dynamics related to environmental changes (Talas et al, 2021; von Hippel et al, 2021). Using a fungal‐specific assay, data on diverse fungal assemblages were retrieved from a series of lake sediment cores in Siberia (Seeber et al, 2022). In this case, most fungal sequences taxonomically annotated were from terrestrial taxa, thereby supporting the changes observed in fungi diversity and assemblage composition recovered from the sediment are closely associated to terrestrial vegetation changes.…”
Section: Beyond Oxygenic Phototrophsmentioning
confidence: 99%
“…Long‐term changes in fungal communities using the sed DNA approach have been recently used to track catchment dynamics related to environmental changes (Talas et al, 2021; von Hippel et al, 2021). Using a fungal‐specific assay, data on diverse fungal assemblages were retrieved from a series of lake sediment cores in Siberia (Seeber et al, 2022). In this case, most fungal sequences taxonomically annotated were from terrestrial taxa, thereby supporting the changes observed in fungi diversity and assemblage composition recovered from the sediment are closely associated to terrestrial vegetation changes.…”
Section: Beyond Oxygenic Phototrophsmentioning
confidence: 99%
“…With the development of next-generation sequencing technologies (Glenn, 2011;Metzker, 2010;Shendure and Ji, 2008), metabarcoding has shown a great potential for reconstructing long-term changes in different biological groups. Several sets of universal PCR primers suitable for sedaDNA studies have been designed for plants (Taberlet et al, 2007), mammals (Giguet-Covex et al, 2014), fish (Miya et al, 2015), fungi (Seeber et al, 2022), diatoms (Stoof-Leichsenring et al, 2012), ostracods (Echeverría-Galindo et al, 2021), and bacteria (Belle and Parent, 2019). Metabarcodes amplified by these primers offer the opportunity to identify the target groups at high taxonomic levels (e.g., species level), and the bias in taxonomic resolution between different taxa can be further complemented by specific primers.…”
Section: Methodological Opportunities and Limitations Of Sedadna Appr...mentioning
confidence: 99%
“…Using both blocking oligos increases detection of mammals and also co-amplifies birds, fish, amphibians and worms (figure 1). Additional organisms, such as diatoms, fungi and lichens, can be amplified through the use of dedicated primers [65][66][67], giving a broader spectrum of biodiversity. Having multiple trophic levels allows a more comprehensive tracing of ecosystem dynamics.…”
Section: The Advantage Of Sedadna Datamentioning
confidence: 99%